Risk factors for sudden cardiac death in adolescents: a systematic review - Rodríguez, Zammir (Medicina Clínica y Social, 2022)
Introduction: Sudden cardiac death is an uncommon result, being in adolescents even more catastrophic for both their family environment and society, for which it is vitally important to identify the factors that can lead a person to be at risk of having this devastating death . Objectives: To determine the risk factors for sudden cardiac death in adolescents. Methods: A systematic review was carried out where all the articles in English and Spanish were taken into account, which were published from 2020 to 2021, on the PubMed and Google Scholar search sites. The following PEO question was used: Population: Adolescents, Exposure: Risk factors, Outcome: Sudden cardiac death. The keywords were: “youth”, in combination with “Risk Factors” and “Sudden Cardiac Death” (used in PubMed). In google scholar, the following terms were used for the advanced search: “Adolescents”, “Sudden Cardiac Death” and “Risk factors”. Articles published since 2015 that met the exclusion criteria were selected. Results: Of the 13 articles for this review regarding sudden cardiac death in adolescents, a variety of causes or risk factors were found that triggered this pathology, finding among these certain causes with greater repetition. Conclusion: Sudden cardiac death has as main risk factors congenital heart disease and genetic load; which we must identify and thus be able to act in a preventive manner reducing their incidence of deaths.